Synthesis of β-SiC in the intermediate layer of corundum coatings based on a sol-gel binder for protecting graphite objects from oxidation - Semchenko, G. D.; Shuteeva, I. Yu.; Ryshchenko, M. I.; Panasenko, M. A.; Ryabkov, Yu. I. (Kluwer Academic/Plenum Publishers, USA, 2011)
A coating is developed for protecting graphite from oxidation at 2023 – 2223 K. The efficiency of the protective action of a corundum coating based on a sol-gel binder increases due to creating a dense intermediate layer between the graphite substrate and the coating as a result of its self-reinforcement with fibers of mullite crystals and -SiC nanoparticles. Components of a modifier and sol-gel binder, but not carbon of the graphite substrate, provide synthesis of β-SiC.
Keywords: graphite oxidation protection; corundum coatings; silicon carbide; mullite; self-reinforcement; dense intermediate layer